Pengembangan Media Kartu Kuartet pada Pembelajaran Pendidikan Pancasila Siswa - Alyusita, Eta; Prananosa, Ahmad Gawdy; Charli, Leo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a product in the from of quartet card media in Pancasila Education learning according to the curriculum and to produce valid, practical and potential effect quartet card media. The type of research used is Research and Development (R & D ) with the model used is ADDIE, the object of this research is class IV students, totaling 22 people. This data research technique was carried out by observation, interviews, documentation, questionnaires, and tests. The results of this study indicate that: 1) the quality of the quartet card media seen from the validity aspect is said to be included in the valid category with an Aiken v coefficient of language experts 0.80, material experts 0.95, media experts 0.77 with a valid category. While the results of the analysis of the assessment of the teacher and student practicality sheets for the quartet card media meet the practical criteria wiyh an average score of 92%, and effective with an average of 0.70% so that it can be concluded that the quartet card media in Pancasila Education learning meets the criteria of valid, practical, and potential effects so that it can be used in learning activities. Keywords: Development ,Pancasila education learning , quarter card media, Elementary School